Association between pre-pregnancy body mass index and gestational diabetes mellitus among pregnant women in Hospital Universiti Sains Malaysia - Yan, Kwok Kar (2021)
Gestational Diabetes Mellitus (GDM) is a condition of glucose intolerance or diabetes with onset or first recognition during pregnancy. Pre-pregnancy body mass index (BMI) is a risk factor for GDM. This study aimed to determine the pre-pregnancy BMI status, the prevalence of GDM, and to identify the association between pre-pregnancy BMI and GDM among pregnant women. This cross-sectional study involved 104 pregnant women at Obstetrics and Gynaecology (O&G) ward in Hospital Universiti Sains Malaysia (Hospital USM), Kelantan. A questionnaire consisted of socio-demographic, anthropometric, and maternal health condition information of the subject was used and the data was collected by self-reporting and referring to the clinical obstetric or medical records. Pre-pregnancy weight was self-reported by the subject and pre-pregnancy BMI was calculated by using weight in kilograms divided by the square of the height in metre. BMI classification of subjects was determined according to the World Health Organization (WHO). The results showed that 8.7%, 43.3%, 26.9%, and 21.2% of subjects had underweight, normal, overweight, and obese pre-pregnancy BMI, respectively. The prevalence of GDM among pregnant women was 29.8%. Pre-pregnancy BMI was not significantly associated with GDM (p= 0.398). However, family history of diabetes in first-degree relatives and maternal age were significantly associated with GDM (p=0.021; p= 0.033). In conclusion, there was no significant association between pre-pregnancy BMI and GDM among pregnant women attending O & G ward in Hospital USM. It is suggested that the high prevalence of obesity or overweight among GDM and non-GDM mothers, high prevalence of first-degree family history of diabetes mellitus, and advanced maternal age may mask the effect of pre-pregnancy BMI on GDM.